Dithienopyrrole as a Rigid Alternative to the Bithiophene π Relay in Chromophores with Second‐Order Nonlinear Optical Properties. Issue 1 (7th October 2014) - Marco, A. Belén; Martínez de Baroja, Natalia; Franco, Santiago; Garín, Javier; Orduna, Jesús; Villacampa, Belén; Revuelto, Alejandro; Andreu, Raquel
Abstract 4H‐Pyranylidene‐containing push‐pull chromophores built around a bithiophene (BT) π relay or a rigidified thiophene‐based unit, namely cyclopenta[1, 2‐b:3, 4‐b′]dithiophene (CPDT) or dithieno[3, 2‐b:2′, 3′‐d]pyrrole (DTP), have been synthesized and characterized. The effect of these different relays on the polarization and the second‐order nonlinear optical (NLO) properties has been studied. For the sake of comparison, the corresponding reported dithieno[3, 2‐b:2′, 3′‐d]thiophene (DTT) derivatives have also been included in the discussion. Replacement of the BT core by a rigidified unit (CPDT, DTP) leads to more polarized systems. Calculated NBO charges and electrochemical measurements show that dithienopyrrole has a remarkable donor character that allows an important charge transfer between the donor and the acceptor. The influence of the rigidification of the BT relay on the NLO responses depends on the acceptor strength. For the weakest acceptor used (thiobarbituric acid), passing from the BT relay to the rigidified units always involves an increase in the μβ0 figure of merit. Nevertheless, for the strongest acceptor (2‐dicyanomethylene‐3‐cyano‐4, 5, 5‐trimethyl‐2, 5‐dihydrofuran (TCF)), a slight increase in μβ0 with respect to the BT chromophore is only observed for the DTP derivative. Thus, rigidification of the BT core is not enough to improve the second‐order nonlinearity and the incorporation of a DTP moiety has proven to be the most efficient approach for this purpose.